Behçet’s disease in children: single-center experience - Çirkinoğlu, Murat Soner (Turk Pediatri Ars, 2019)
AIM: In this study, it was aimed to summarize the demographics, and clinical and laboratory findings of children who were diagnosed as having Behçet’s disease, and also to determine the efficacy, duration, and adverse effects of the treatments. MATERIAL AND METHODS: The records of 34 patients who were diagnosed according to the International Behçet Study Group criteria between 1980 and 2013 in the Department of Pediatric Nephrology and Rheumatology, Hacettepe University Faculty of Medicine, were retrospectively reviewed and all demographic and clinical features were recorded. In the light of these data, the sex and age distribution, clinical and laboratory findings, most commonly preferred treatment approaches, efficacy of treatments, and adverse effects during treatment were analyzed. RESULTS: Of the 34 children with Behçet’s disease, 18 (53%) were male and 16 (47%) were female, and the mean age was 11.18±3.34 years. There was no significant difference in age distribution of the male and female patients (p<0.05). In 97% (n=33) of the patients, the first symptom was recurrent oral aphthae. In order of frequency, the other mucocutaneous findings were pseudofoliculitis and pustular lesions (82%), genital ulcers (62%), and pathergy positivity (50%). System involvements in order of frequency were as follows: joint findings (38%), ocular findings (35%), vascular involvement (32%), neurologic involvement (18%), gastrointestinal involvement (5.8%), and pulmonary involvement (5.8%). Colchicine was the most commonly preferred drug (88%). Steroids were added to treatment in patients with skin involvement. Azathioprine was added in patients with uveitis. Anticoagulant therapy, cyclophosphamide, and anti-tumor necrosis factor-alpha were added in patients with vascular involvement. In patients with gastrointestinal system involvement, sulfasalazine was added to treatment. Diarrhea was the most common adverse effect in patients who used colchicine. In the patients who used steroid treatment, gastrointestinal symptoms such as unintentional weight gain, acne, and agitation were observed (17%). One patient who received interferon treatment had symptoms of depression and agitation. CONCLUSION: The aim of this study was to review the general characteristics of pediatric patients with Behçet’s disease and to emphasize the importance of early diagnosis and correct treatment in terms of mortality and morbidity.